Kaitan Ergonomi dengan Nyeri Punggung Bawah pada Dokter Gigi Praktik Mandiri di Jambi - Willia Novita Eka Rini; Tiara Zudiannisa; Hendra Dhermawan Sitanggang; Budi Aswin; Ashar Nuzulul Putra; Zilzikridini Wijayanti (Pusat riset dan Inovasi Nasional, 2025)
Background: Low back pain (LBP) is still one of the health problems, including in the dental profession. Doctor Dentists have a risk of experiencing Low Back Pain (LBP) when viewed from their static work activities. work activities that are static. The purpose of this study was to determine relationship between ergonomic factors and complaints of Low Back Pain (LBP) in general dentists practicing independently in Jambi City. general dentists practicing independently in Jambi City. Methods: This study is a quantitative study with an observational observational research design and using a cross sectional research design. The study population was general dentists practicing in Jambi City, totaling 204 people. Respondents in this study 70 people. Data collection using the ODI questionnaire for measurement LBP measurement, fingertip pulse oximeter for measurement of workload, Rapid Upper Limb Assessment (RULA) for work posture measurement, vibration meter for vibration measurement, and lux meter for lighting measurement. Data analysis using chi-square statistical test version 24. Results: The results showed the prevalence of complaints of Low Back Pain (LBP) in dentists was 60%. dentists amounted to 60%. The statistical test results show that the variables workload (p=0.000 <0.05), work posture (p=0.000 <0.05), length of work (p = 0.000 < 0.05), repetition (p = 0.003 < 0.05), lighting (p = 0.415 > 0,05). Conclusion: There is a relationship between workload, work posture, work duration, repetition with complaints of Low Back Pain (LBP) and there is no relationship between workload, work posture, work duration, repetition and lighting